2010
DOI: 10.4314/njm.v19i3.60221
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Perception And Practice Of Female Genital Mutilation Among Expectant Mothers In Jos University Teaching Hospital Jos, North-Central Nigeria

Abstract: Background Methodology Results Conclusion: WHO estimates that some 130 million women worldwide are affected, and every year another 2 million girls and young women are at risk of undergoing the practice of FGM.Although Nigeria has a prevalence of 19% in 2003,a reduction from 25% prevalence of 1999 national survey, it still has high absolute number of cases with wide regional variation. The awareness and perception of expectant mothers may give an insight as to what awaits their unborn daughters and have a bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
5
11
2
Order By: Relevance
“…The 79.3 % awareness of FGM in this study is high; it is lower than the 91.4 % from Kano [13] and 94.6 % from Jos [16], all in northern Nigeria. However it is higher than the 53 % reported by the NDHS (2008) for women residing in rural area and also higher than the 39.4 % reported by the same report for the northwest zone [6].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The 79.3 % awareness of FGM in this study is high; it is lower than the 91.4 % from Kano [13] and 94.6 % from Jos [16], all in northern Nigeria. However it is higher than the 53 % reported by the NDHS (2008) for women residing in rural area and also higher than the 39.4 % reported by the same report for the northwest zone [6].…”
Section: Discussioncontrasting
confidence: 67%
“…However, these uncommon types are commonly practiced in other parts of the country [6] especially in the southern parts [14,15] and are also practiced in the urban areas in northern Nigeria [6,9,13,16]. About four of ten respondents that were aware of FGM had experienced it, and 56 % of them had Gishiri cut while 49 % had experienced Angurya cuts.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the prevalence of FGM of 47.8% observed in this study is similar to the 49.6% reported from Abakaliki south-east Nigeria [26] but is lower than the 65.5% reported from a community based study in Ilorin north-central Nigeria [27]. It is however higher than the 39.1% reported in Birnin Kudu north-west Nigeria [14], the 31.3% from Jos also in north-central [28] and the 13.1% among infants in Kano, north-west Nigeria [16]. The commonest type of FGM observed in this study was Type I, which is similar to findings reported from Kano [16] but its prevalence of 73.5% is however lower than the 96.2% noted in Kano.…”
Section: Discussionsupporting
confidence: 54%
“…Despite the fact that there is no scriptural support for FGC in the Koran or the Bible, many women cite religious duty or cultural tradition as reasons for continuing FGC in their communities. [24][25][26][27][28] Although it is challenging to find clear evidence of FGC in early literature, FGC has been present in the regions of Africa where it is practiced for hundreds, if not thousands, of years. Writing in approximately 24 AD, Strabo states, "One of the customs most zealously observed among the Aegyptians is this, that they rear every child that is born, and circumcise the males, and excise the females.." 29 No single religion appears to be associated with a higher prevalence of FGC across locations where FGC is practiced.…”
Section: Educationmentioning
confidence: 99%